Combined cytotoxic effects of pesticide mixtures present in the Chinese diet on human hepatocarcinoma cell line. (September 2016) - Ma, Mengmeng; Chen, Chen; Yang, Guiling; Li, Yun; Chen, Zhijun; Qian, Yongzhong
Abstract: Consumers might be simultaneously exposed to several pesticide residues contained in their food. Based on the results of previous studies, 20 pesticides were selected due to their high exposure levels to which the Chinese population is likely exposed through the diet. The purpose of this study was to measure the cytotoxicity of these pesticides in HepG2 cells in vitro, as an alternative approach to assess the toxicity of chemicals. Then, the pesticides and some of the mixtures with comparatively high cell-proliferating inhibitory activities were selected to test the cellular ROS level and apoptosis-related protein Caspase-3/7 content in HepG2 cells. The combined effects of these pesticide mixtures with the prediction was based on a combination index (CI)-isobologram equation and the pesticide combinations exhibited various types of interactions (synergism, antagonism, and additivity). Two individuals, one binary combinations, and three uniform design (UD) mixtures of the pesticides were found to have significant cytotoxic effects, along with significant time- and dose-dependent induction of caspase-3/7 activity in vitro, indicating that cytotoxicity caused by these pesticides might be attributed to the pro-oxidative and apoptosis induced potential. Graphical abstract: Highlights: Cytotoxicity of high-risk pesticides was evaluated on human HepG2 cell lines. Combined effects of the pesticides were assessed using combination index method. Increasing ROS and caspase-3/7 levels were found in some pesticides pairings. The mediated activation of caspase-3/7 and ROS level are attributed to apoptosis.